Development of an Efficient Strategy to Improve Extracellular Polysaccharide Production of Ganoderma lucidum Using L-Phenylalanine as an Enhancer - Ma, Zhongbao; Xu, Mengmeng; Wang, Qiong; Wang, Feng; Zheng, Huihua; Gu, Zhenghua; Li, Youran; Shi, Guiyang; Ding, Zhongyang (Frontiers in Microbiology, 2019)
Ganoderma lucidum has been a well-known species of basidiomycetes for a long time, and has been widely applied in the fields of food and medicine. Based on the simulation results of model iZBM1060 in our previous research, the effect of L-phenylalanine on G. lucidum extracellular polysaccharides (EPSs) was investigated in this study. EPS production reached 0.91 g/L at 0.4 g/L L-phenylalanine after a 24 h culture, which was 62.5% higher than that of control (0.56 g/L). Transcriptome and genome analysis showed that L-phenylalanine deaminase and benzoate 4-hydroxylase (related to L-phenylalanine metabolism) were significantly up-regulated, while the cell wall mannoprotein gene was down-regulated. Transmission electronic microscopy (TEM) and atomic force microscopy results showed that the cell wall thickness decreased by 58.58%, and cell wall porosity increased in cells treated with L-phenylalanine, which probably contribute to the increasing EPS production. This study provides an efficient strategy for fungal polysaccharide production with high output and low cost.